A Thom isotopy theorem for nonproper semialgebraic maps - Dias, Luis Renato Gonçalves; Ramos, Giovanny Barrera (Topological Methods in Nonlinear Analysis, 2026)
We prove a version of the Thom isotopy theorem for nonproper semialgebraic maps $f\colon X→ \mathbb R^m$, where $X \subset\mathbb R^n$ is a semialgebraic set and $f$ is the restriction to $X$ of a smooth semialgebraic map $F\colon\mathbb R^n→ \mathbb R^m$.